The Impact of Stannous, Fluoride Ions and Its Combination on Enamel Pellicle Proteome and Dental Erosion Prevention - Algarni, A. A.; Mussi, M. C. M.; Moffa, E. B.; Lippert, F.; Zero, D. T.; Siqueira, W. L.; Hara, A. T. (PLOS ONE, 2015)
Objectives To compare the effects of stannous (Sn) and fluoride (F) ions and their combination on acquired enamel pellicle (AEP) protein composition (proteome experiment), and protection against dental erosion (functional experiment). Methods In the proteome experiment, bovine enamel specimens were incubated in whole saliva supernatant for 24h for AEP formation. They were randomly assigned to 4 groups (n=10), according to the rinse treatment: Sn (800ppm/6.7mM, SnCl2), F (225ppm/13mM, NaF), Sn and F combination (Sn+F) and deionized water (DIW, negative control). The specimens were immersed 3× in the test rinses for 2min, 2h apart. Pellicles were collected, digested, and analyzed for protein content using liquid chromatography electrospray ionization tandem mass spectrometry. In the functional experiment, bovine enamel specimens (n=10) were similarly treated for pellicle formation. Then, they were subjected to a five-day erosion cycling model, consisting of 5min erosive challenges (15.6 mM citric acid, pH 2.6, 6×/d) and 2min treatment with the rinses containing Sn, F or Sn+F (3×/d). Between the treatments, all specimens were incubated in whole saliva supernatant. Surface loss was determined by profilometry. Results Our proteome approach on bovine enamel identified 72 proteins that were common to all groups. AEP of enamel treated with Sn+F demonstrated higher abundance for most of the identified proteins than the other groups. The functional experiment showed reduction of enamel surface loss for Sn+F (89%), Sn (67%) and F (42%) compared to DIW (all significantly different, p<0.05). Conclusion This study highlighted that anti-erosion rinses (e.g. Sn+F) can modify quantitatively and qualitatively the AEP formed on bovine enamel. Moreover, our study demonstrated a combinatory effect that amplified the anti-erosive protection on tooth surface.